Brand Awareness And Consumer Satisfaction Drive Customer Loyalty In Skincare Products: Kesadaran Merek Dan Kepuasan Konsumen Mendorong Loyalitas Pelanggan Pada Produk Skincare - Amara Putri D.U; Rohma Puji A; Salsa Nabilah P.R; Silva Nur L.F; Sigit Hermawan (Proceedings of The ICECRS, 2024)
General Background The global beauty industry experiences rapid growth driven by rising cosmetic demand and international beauty trends. Specific Background Skintific, an international cosmetic company formulating items in Canada, recently entered the highly competitive market, necessitating strong marketing strategies to retain buyers. Knowledge Gap Despite extensive research on cosmetics, previous empirical studies present conflicting evidence regarding whether physical item characteristics and corporate recognition directly determine long-term consumer retention. Aims This study investigates how brand awareness and product quality shape customer loyalty, specifically examining consumer satisfaction as a mediating variable among university students. Results Path analysis reveals that brand awareness and product quality positively determine consumer satisfaction. Interestingly, product quality does not directly dictate customer loyalty, whereas brand awareness and consumer satisfaction possess a significant direct relationship with buyer retention. Furthermore, consumer satisfaction successfully mediates the pathways from both brand recognition and physical characteristics to final customer loyalty. Novelty This research demonstrates that physical cosmetic characteristics alone fail to retain buyers; achieving long-term retention strictly requires building preliminary post-purchase fulfillment. Implications Cosmetic companies must prioritize comprehensive marketing campaigns that build corporate recognition and ensure post-purchase fulfillment rather than relying exclusively on item features to secure long-term buyer retention. Highlights: • Corporate recognition directly establishes long-term buyer retention. • Physical item characteristics require mediation to successfully retain users. • Post-purchase fulfillment bridges the gap between item features and continued repurchasing. Keywords: Brand Recognition, Product Characteristics, Post-Purchase Fulfillment, Buyer Retention, Mediating Variable